STUDI KEBUTUHAN NYATA AIR BERSIH PER KAPITA PADA KOTA BANDAR LAMPUNG - Sinia, Ria Oktaviani; Susilo, Gatot Eko (Jurnal Profesi Insinyur Universitas Lampung, 2021)
As we already known, along with the increasing and bigger of the population, the number of life necessities that must be fulfilled is also getting bigger. One of main necessities of life that must always be fulfilled are clean water. This study aims to: (1) to investigate the amount of clean water demand per capita in Bandar Lampung City; (2to identify all the factors that affect theamount of clean water needs, (3) to counting the amount of clean water consumption costs, (4) to compare this results than research before. Location of this research are at Bandar Lampung City area which covers 20 sub-districts and 126 villages. Data collection on clean water needs was carry out using a questionnaire that distributed to 126 households randomly. The conclution of this research, are: (1) The amount of clean water per capita at Bandar Lampung are about 130.44 ltr/person/day. (2) The factors that influence the amount of clean water used, are: number of family members, education status, type of work, number of vehicle ownership, and ease of obtaining water. The cost of clean water needs issued at Bandar Lampung City in every month ranges from Rp. 127,267.00 up to Rp. 187,449, 00. (4) The results that obtained in this study are far different from the results of Kindler and Russel's (1984), which stated that the average water use for households is 295 ltr /person/day. But the results obtained in this study approached the Planning Criteria Set by the Directorate General of Human Settlements, Public Works Agency in 1996, which stated that the Big City, which has population of 500,000 - 1,000,000 people, will has domestic water needs about 120 ltr/person/day until 150 ltr/person/day.